Clinical characterizations and molecular genetic study of two co-segregating variants in PDZD7 and PDE6C genes leading simultaneously to non-syndromic hearing loss and achromatopsia - Zahra Nouri; Akram Sarmadi; Sina Narrei; Hamidreza Kianersi; Farzan Kianersi; Mohammad Amin Tabatabaiefar (BMC Medical Genomics)
Abstract Background Autosomal recessive non-syndromic hearing loss (NSHL) and cone dystrophies (CODs) are highly genetically and phenotypically heterogeneous disorders. In this study, we applied the whole exome sequencing (WES) to find the cause of HL and COD in an Iranian consanguineous family with three affected individuals. Methods Three members from an Iranian consanguineous family who were suffering from NSHL and visual impairment were ascertained in this study. Comprehensive clinical evaluations and genetic analysis followed by bioinformatic and co-segregation studies were performed to diagnose the cause of these phenotypes. Data were collected from 2020 to 2022. Results All cases showed congenital bilateral NSHL, decreased visual acuity, poor color discrimination, photophobia and macular atrophy. Moreover, cornea, iris and anterior vitreous were within normal limit in both eyes, decreased foveal sensitivity, central scotoma and generalized depression of visual field were seen in three cases. WES results showed two variants, a novel null variant (p.Trp548Ter) in the PDE6C gene causing COD type 4 (Achromatopsia) and a previously reported variant (p.Ile84Thr) in the PDZD7 gene causing NSHL. Both variants were found in the cis configuration on chromosome 10 with a genetic distance of about 8.3 cM, leading to their co-inheritance. However, two diseases could appear independently in subsequent generations due to crossover during meiosis. Conclusions Here, we could successfully determine the etiology of a seemingly complex phenotype in two adjacent genes. We identified a novel variant in the PDE6C gene, related to achromatopsia. Interestingly, this variant could cooperatively cause visual disorders: cone dystrophy and cone-rod dystrophy.